THE EFFECT OF INTERACTION BETWEEN LEARNING MODELS AND CRITICAL THINKING ON STUDENTS' MATHEMATICAL COMMUNICATION ABILITY IN ELEMENTARY SCHOOL - Parwines, Zutri (Proceeding of International Conference on Islamic Education (ICIED); Vol 7 No 1 (2022): Proceeding of International Conference on Islamic Education (ICIED), 2022)
The purpose of this study is to determine whether there is an interaction between learning models and critical thinking in the mathematical communication skills of elementary school students. This type of research is experimental quantitative research. This research was conducted in two schools, namely SD Islam At Taubah and SD Islam At Taqwa in East Jakarta. The sample of this study consisted of 60 students with 2 classes, namely the control class and the experimental class. The results of the analysis of the mathematical communication ability test show that the data is normally distributed and has a homogeneous variance. This study used two-way ANOVA analysis. From the ANOVA calculation, there is an interaction between the learning model and critical thinking in students' mathematical communication skills.